2021
DOI: 10.14309/01.ajg.0000798796.64423.34
|View full text |Cite
|
Sign up to set email alerts
|

P049 Investigation of Liver Diseases by Ultrasound in Patients With Inflammatory Bowel Disease

Abstract: BACKGROUND: Inflammatory Bowel Disease (IBD), which can be divided into Crohn’s Disease (CD) and Ulcerative Colitis (UC), is an immune mediated disease featured by gastrointestinal tract involvement. Hepatic disease, such as non-alcoholic fatty liver disease (NAFLD), cirrhosis, cholelithiasis, hepatic thromboembolic events and primary sclerosing cholangitis (PSC) are some hepatic complications presented by IBD patients. Since these hepatic disorders have a higher prevalence in IBD patients, ultraso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…In this context, our study showed a US prevalence of NAFLD of 23% in IBD patients. These data are in line with recent epidemiological investigations that showed a US prevalence of 20-50% [12,29,30,34]. Given that IBD is a risk factor for NAFLD, this result underlines the importance of performing hepatic US in at-risk patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this context, our study showed a US prevalence of NAFLD of 23% in IBD patients. These data are in line with recent epidemiological investigations that showed a US prevalence of 20-50% [12,29,30,34]. Given that IBD is a risk factor for NAFLD, this result underlines the importance of performing hepatic US in at-risk patients.…”
Section: Discussionsupporting
confidence: 90%
“…Another study showed the US prevalence of NAFLD in IBD patients treated with biological therapy at 54% [29]. Similar results were obtained by Shintaku et al, with a US prevalence of NAFLD of 45% among 71 enrolled IBD patients [30]. In addition, due to the newly proposed nomenclature of metabolic-associated fatty liver disease (MAFLD), there is a need for continuous evaluation of the clinical features of these patients, especially from a metabolic perspective [7].…”
Section: Diagnostic Approaches In Nafldsupporting
confidence: 52%